2022
DOI: 10.1039/d2cc00163b
|View full text |Cite
|
Sign up to set email alerts
|

Redox-active alkylsulfones as precursors for alkyl radicals under photoredox catalysis

Abstract: Visible-light photoredox catalytic method for the generation of alkyl radicals using redox-active alkylsulfones to form a new C–C bond is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This is consistent with a spontaneous SET from 23 0 to 24, as supported by the results from spectroscopic analyses. The C(sp 3 )-SO 2 bond of the metastable intermediate 27 was cleaved through a low activation energy (DG ‡ (TS 27-28 ) = 9.2 kcal mol −1 ) path forming an excited-state complex between the tertiary carbon radical, the tetrazolyl sulnate anion, and the pyrene cation (28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with a spontaneous SET from 23 0 to 24, as supported by the results from spectroscopic analyses. The C(sp 3 )-SO 2 bond of the metastable intermediate 27 was cleaved through a low activation energy (DG ‡ (TS 27-28 ) = 9.2 kcal mol −1 ) path forming an excited-state complex between the tertiary carbon radical, the tetrazolyl sulnate anion, and the pyrene cation (28).…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Furthermore, reductive activation of alkyl sulfones through single electron transfer (SET) has enabled radical functionalization reactions under mild conditions. [24][25][26][27][28] During our investigations into radical generation from sulfones using PAHs as photocatalysts, we observed the formation of alkylated PAHs. Building on this observation, we envisioned that a photo-induced process might provide a powerful solution to the issue of regioselective functionalization of PAHs without resorting to photocatalysts or precious metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022 Chatterjee and co-workers reported a photoredox-catalyzed desulfonylative C–C bond formation reaction. 30 They used Ir(ppy) 3 as the catalyst and afforded the alkylation and allylation reactions using aryl and allyl sulfone precursors 55 and 56 (Scheme 14 ). Mechanistically is has some similarity with the work of Wu and Xiao (Schemes 3 and 4).…”
Section: Photoredox-catalyzed C–c Bond Formationmentioning
confidence: 99%
“…Building on the work of our group and others with regards to the application of sulfones in catalysis, we show that visible-light photoredox catalysts can be employed to promote the reductive desulfonylation of tertiary alkylsulfones and their reaction with gem -difluoroalkenes (Scheme c). Previous reports from our group, the Sengoku/Yoda group, and the Chatterjee group have shown that carbon radicals can be generated from alkylsulfones either through single electron reduction promoted by Zn and 1,10-phenanthroline (phen) or visible-light-induced reduction. The resulting alkyl radicals can be reacted with various acrylate derivatives in a Giese-type reaction but the scope of these transformations remained limited.…”
Section: Introductionmentioning
confidence: 99%